2020
DOI: 10.3390/ijerph18010012
|View full text |Cite
|
Sign up to set email alerts
|

The Direct and Indirect Costs of Colorectal Cancer in Vietnam: An Economic Analysis from a Social Perspective

Abstract: The incidence and mortality of colorectal cancer (CRC) has increased rapidly in Vietnam, but the economic burden of this disease has never been estimated. We estimate the direct and indirect cost of CRC patients in Vietnam in 2018 using a prevalence-based approach and human capital method. The total economic cost of CRC was VND 3041.88 billion (~$132.9 million), representing 0.055% of the 2018 gross domestic product. Notably, indirect costs comprised 83.58 % of the total cost, 82.61% of which is future income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Consequently, the cost of patient companions’ absenteeism due to accompanying patients as well as patient care was high. The results of the present study are is inconsistent with those of the studies by Tran et al (2021), 11 Vahdatimanesh et al (2017), 14 and Byun et al (2014), 13 in which it had been reported that mean indirect costs were the highest ones. The difference can be because of the several premature deaths due to colorectal cancer and their related costs in these 3 studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, the cost of patient companions’ absenteeism due to accompanying patients as well as patient care was high. The results of the present study are is inconsistent with those of the studies by Tran et al (2021), 11 Vahdatimanesh et al (2017), 14 and Byun et al (2014), 13 in which it had been reported that mean indirect costs were the highest ones. The difference can be because of the several premature deaths due to colorectal cancer and their related costs in these 3 studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Ngcamphalala et al ( 10 ) reported considerable costs of cervical cancer in Eswatini, with indirect costs accounting for 27% (USD5.3 million) of total expenditures and productivity loss due to premature mortality accounting for 67% (USD3.5 million). Likewise, a Vietnamese study describing the burden of colorectal cancer reported that the productivity costs of the cancer were about 83.58% of the overall cost, with 82.61% of future income loss occurring during the productive years ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer mortality and morbidity are high in countries where the HPV vaccine is not yet obligatory, such as Indonesia ( 6 ). And, studies from these developing countries report that cancer-related productivity loss causes about 60%–85% of the economic burden ( 4 , 11 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cost-of-illness studies are critical to informing policy decisions on cancer prevention and control, cost-effectiveness evaluations and improving public health. 23 Costs of CRC have been assessed in many countries, such as Iran, 24 Vietnam, 25 New Zealand 26 and across the European Union, 23 and all studies have demonstrated high costs of CRC and substantial burden on the healthcare system. However, evidence on costs of CRC in China is limited.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%